APLIKASI QUIZIZZ DAN PRESTASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR ISLAM ATHIRAH KOTA MAKASSAR - Albar; Safei; M. Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2023)
This research aims to describe the effect of using the Quizizz application on student learning outcomes at the Athirah Racing Center Islamic Elementary School, Makassar City. This type of research is quantitative research with an ex post facto method. The number of respondents to this research was 41 people, the data collection technique used a questionnaire instrument and documentation format which was analyzed using descriptive and inferential statistics by carrying out the F test. Based on descriptive statistical analysis carried out at the Athirah Racing Center Islamic Elementary School, Makassar City showed that the use of the Quizizz application was significant. has an influence of 66.2% on the learning outcomes of students specifically for Islamic Religious Education (PAI) subjects at the Athirah Racing Center Islamic Elementary School (SD) Makassar City. While the remaining 33.8% is influenced by other factors including; intellectual intelligence, facilities and infrastructure, methods and models used by educators, and learning atmosphere.